Respon Pertumbuhan dan Hasil Tanaman Jagung Pulut Ungu (Zea mays L. var ceratina) Varietas Jantan F1 Akibat Kombinasi Populasi Tanaman dan Dosis Pupuk Organik - Fajar Rochman; Priyadi Priyadi; Lina Budiarti; Hery Sutrisno (Politeknik Negeri Lampung, 2023)
The research aims to determine the effect of different combinations of plant population and organic fertilizer dosages on the growth and yield of the best male F1 variety of purple sticky corn. This experiment used a complete randomized block design consisting of six treatments and repeated four times. The treatments consisted of: A. (66.666 plants/ha with 5 ton/ha); B. (66.666 plants/ha with 10 ton/ha); C (53.333 plants/ha with 5 ton/ha); D (53.333 plants/ha with 10 ton/ha); E (40.000 plants/ha with 5 ton/ha); F (40.000 plants/ha with 10 ton/ha). The observed plant responses consisted of: plant height, leaf area, plant dry weight, weight of cobs with husk per plant, weight of cobs without husk per plant, cob length, and cob diameter. The results of this study showed that different combinations of plant population and organic fertilizer dosages had an effect on the plant height, plant height, leaf area at, plant dry weight, weight of cobs with husk per plant, weight of cobs without husk per plant, cob length, and cob diameter of male F1 Jantan variety of purple sticky corn. The combination of 40,000 plants/ha plant population with 5 tons/ha of organic fertilizer gave the best yield for male F1 Jantan variety of Pulut Ungu corn plants.